2021
DOI: 10.3389/fmolb.2021.567730
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Nine Apoptosis-Related Genes Signature Predicting Overall Survival for Kidney Renal Clear Cell Carcinoma and its Associations with Immune Infiltration

Abstract: Background: This study was designed to establish a sensitive prognostic model based on apoptosis-related genes to predict overall survival (OS) in patients with clear cell renal cell carcinoma (ccRCC).Methods: Obtaining the expression of apoptosis-related genes and associated clinical parameters from online datasets (The Cancer Genome Atlas, TCGA), their biological function analyses were performed through differently expressed genes. By means of LASSO, unadjusted and adjusted Cox regression analyses, this pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 46 publications
2
12
0
Order By: Relevance
“…40 In the IFI44 family, the interferon-induced protein 44-like (IFI44L), a momentous paralog of IFI44, is a type I interferon-stimulated gene (ISG). It has been reported that the depletion of IFI44L enhances the migration, invasion and lung metastasis of hepatocellular carcinoma by activating the Met/Src signaling pathway, 41 while in ccRCC, patients with high IFI44 expression exhibit reduced survival, 42 consistent with our findings. In addition, higher levels of M1 macrophages and M2 macrophages 43 were observed in tumor sections with high IFI44 expression.…”
Section: Discussionsupporting
confidence: 92%
“…40 In the IFI44 family, the interferon-induced protein 44-like (IFI44L), a momentous paralog of IFI44, is a type I interferon-stimulated gene (ISG). It has been reported that the depletion of IFI44L enhances the migration, invasion and lung metastasis of hepatocellular carcinoma by activating the Met/Src signaling pathway, 41 while in ccRCC, patients with high IFI44 expression exhibit reduced survival, 42 consistent with our findings. In addition, higher levels of M1 macrophages and M2 macrophages 43 were observed in tumor sections with high IFI44 expression.…”
Section: Discussionsupporting
confidence: 92%
“…For example, MALAT1 is a lncRNA that acts as a marker in various cancers [ 39 ], and miR-182-5p can reduce the proliferation of ccRCC by binding with MALAT1 [ 38 ]. C4orf3 [ 40 ] and MDK [ 41 ] were also used as markers to evaluate ccRCC. Research on the remaining genes in ccRCC is rare, although these genes play important roles in other cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Despite early surgical treatment, 30% of patients with a localized tumor eventually develop metastases, and the five-year overall survival rate of metastatic KIRC is only 12% [2][3][4]. Although immune-checkpoint and targeted therapeutics inhibitors have changed the landscape of treatment for KIRC, most patients have never experienced significant clinical benefits [5,6]. Therefore, it is essential to reveal the underlying molecular mechanisms of KIRC and find more powerful diagnostic biomarkers or therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%